The Effect of Problem-Based Learning (PBL) E-Modules on Science Literacy, Critical Thinking, and Creativity - Muchsin, Ali; Vebrianto, Rian; Diki; Al-Khairi, Nidya (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2025)
The science literacy, critical thinking, and creativity skills of Grade VIII students at SMPN 4 Rengat Barat are still relatively low. This level is characterized by a tendency to copy other students’ assignments, remaining silent when they do not understand the material, and providing logical answers with little creativity. This study analyzes the effect of using Problem-Based Learning (PBL) e-modules on students’ science literacy, critical thinking, and creativity at SMPN 4 Rengat Barat. This research employs a quantitative approach with an experimental method. Data were collected using paper-and-pencil tests to measure science literacy, critical thinking, and creativity, as well as questionnaires to assess the use of e-modules. The study population consisted of Grade VIII students, with the research sample comprising class VIIIA and VIIIB, totaling 36 students in the control group and 36 in the experimental group. Data were analyzed using the t-test. The study’s results show that the use of PBL-based e-modules has a significant and positive effect on science literacy among Grade VIII students at SMPN 4 Rengat Barat, contributing 26.6% and categorized as moderate. The impact of PBL-based e-modules on students’ critical thinking is also significant and positive, contributing 28.5% and categorized as moderate. Furthermore, the effect of PBL-based e-modules on students’ creativity is significant and positive, with a 24% contribution, still within the moderate category.